Nerve-Sparing Radical Vaginectomy: Two Case Reports and Description of the Surgical Technique. Issue 4 (1st April 2009) - Raspagliesi, Francesco; Ditto, Antonino; Martinelli, Fabio; Hanozet, Francesco; Solima, Eugenio; Grijuela, Barbara; Haeusler, Edward; Fontanelli, Rosanna
Abstract : Background: Radical vaginectomy (RV) is related to significant bladder dysfunctions. We describe 2 cases of RV with nerve-sparing technique (NSRV). Case Reports: A 58-year-old woman with a diagnosis of locally advanced cervical cancer underwent neoadjuvant chemotherapy with local and nodal progression of disease. The patient underwent NS radical hysterectomy plus NSRV, with prompt recovery of bladder function. A 14-year-old adolescent girl with a diagnosis of recurrent embryonal-botryoidal rhabdomyosarcoma was referred to us. She underwent 6 courses of chemotherapy with persistent disease. She then underwent NSRV. Two months after the surgical procedure, she was able to void the bladder. Conclusions: These are the first 2 cases of NSRV reported in literature. This new surgical technique is feasible, with prompt recovery of bladder function.